"Naš car ima za svašta zakon" - Vervaet, Stijn (Slavistična revija, 2009)
The article examines the narrative construction of national identity and the reception of social modernization in Bosnian literature of the Austro-Hungarian period (1878-1918). Based on the examples from the works by Edhem Mulabdić, Petar Kočić, Svetozar Ćorović, and Radovan Tunguz-Perović Nevesinjski, the author explains why many Bosnian authors consider the discussion of social medernization of key importance for the "survival of national identity" of the ethnic community with which they identify. It is also argues that the modernization processes in works of many Bosnian authors is tantamount to the specific, i.e., colonial, policies, carries out by the dual monarchy in Bosnia and Herzegovina.
Keywords: 1878/1918; Austria-Hungary; Avstro-Ogrska; bosanska književnost; bosanskohercegovska književnost; narodna identiteta; pisatelji